Introduction to dye sensitized solar cell (DSC) - Zou, Xin (2013)
DSC is a low-cost, high-efficiency solar cell based on dye-sensitized colloidal TiO2 films, converting solar energy to electric energy. Also known as Photoelectrochemical cell or Graetzel cell. [1st Award]